Exploring School Personnel’s Conceptions on Managing Instruction and Services for High School Aeta Students - Payad, Arlan (JPAIR Multidisciplinary Research, 2024)
The exploratory study featured four high schools and their personnel's conceptions of better instruction and school services for Aeta students. The researcher used open-ended questions to interview 42 public school personnel. Sharing their strengths, weaknesses, and experiences related to inclusiveness towards the Indigenous students, the teachers, administrators, and support service personnel hinted at their training needs revolving around competencies in producing investigative articles on the educational needs of the Aetas, collaborating with co-workers in synergistically servicing the indigenous, greater awareness of ethical protocol in engaging with the Indigenous in service provision contexts, reflecting more intensively on personal efficacy in teaching non-mainstream students, re-tooling given cultural competence, knowing more of the culture and values of the Aetas, and championing more pro-actively the needs of the Indigenous, particularly in the educational and livelihood spheres of their life. Thematic analysis and interpretation brought to the fore the personnel's strong support for a curriculum that is specifically designed for the Aetas, support systems strengthened to empower the personnel further inclusiveness-wise, differentiated instruction facilitated with animation of Indigenous knowledge and learner centeredness, inclusiveness training for the personnel, and inclusive community events, and counseling specifically for Aetas.
Keywords: Education; Double Reduction pinclusive education management; cultural competence; inclusiveness training; interview; thematic analysis; Pampanga; Philippines